ADFS authentication services for cloud infrastructure - Демчинский, Владимир Васильевич (Ukrainian Information Security Research Journal, 2015)
Currently the use of cloud computing is becoming increasingly important. The main feature of cloud computing -providing services remotely, to the extent needed and inthe required time, a flexible control system. However, theuse of cloud computing poses new threats to information security, but also requires a rethinking of the traditional threats to network infrastructure. One of the key tasks ofsecurity - authentication also requires a new approach.The article discusses the security of cloud infrastructure and, in particular, the use of Active Directory Federation Services for authentication.